A diagnostic study of Nigeria's non-oil export sector : findings and recommendations - Central Bank of Nigeria; Nigeria Export and Import Bank (NEXIM) (Abuja, Nigeria : Central Bank of Nigeria/Nigeria Export and Import Bank, 1999)
The basic objective of this study is to evaluate the performance of the non-oil sector with a view to identifying the factors responsible for the poor performance.
A CBN/NEXIM Project
Includes bibliographical references
osc 02/08/2016
Loans
Keywords: Export; Nigeria